UNC80 mutation causes a syndrome of hypotonia, severe intellectual disability, dyskinesia and dysmorphism, similar to that caused by mutations in its interacting cation channel NALCN. Issue 6 (6th November 2015) - Perez, Yonatan; Kadir, Rotem; Volodarsky, Michael; Noyman, Iris; Flusser, Hagit; Shorer, Zamir; Gradstein, Libe; Birnbaum, Ramon Y; Birk, Ohad S
Abstract : Background: A syndrome of profound hypotonia, intellectual disability, intrauterine growth retardation with subsequent failure to thrive, dyskinesia and epilepsy was diagnosed in Bedouin Israeli families. Mild dysmorphism was evident: plagiocephaly, broad forehead with prominent nose, smooth philtrum and congenital esotropia. We set out to decipher the molecular basis of this syndrome. Methods: Genome-wide linkage analysis and fine mapping were done. Whole exome sequencing data were filtered for candidate variants within locus. Validation and segregation of the mutation was assayed via Sanger sequencing. UNC80 expression pattern was analysed through reverse transcription PCR. Results: Homozygosity mapping followed by fine mapping identified a 7.5 Mb disease-associated locus (logarithm of odds score 3.5) on chromosome 2. Whole exome and Sanger sequencing identified a single homozygous nonsense mutation within this locus, segregating within the families as expected for recessive heredity and not found in a homozygous state in 150 Bedouin controls: c.151C>T, p.(R51*) in UNC80 . Conclusions: The syndrome described is caused by a mutation in UNC80, truncating most of the 3258 amino acids highly conserved encoded protein, that has no known motifs. UNC80 bridges between UNC79 and the cation channel NALCN, enabling NALCN's role in basal Na + leak conductance in neurons, essential for neuronal function. The phenotype caused by the UNC80 mutation resembles that previously described for homozygous NALCN mutations.